The effect of features of text (word length and frequency) on the Iranian dyslexic students' eye movements - Masood Sharifi; mohammad kaghazloo; Majid Firouzkouhi Berenjabadi; Mina Bandeh Pour (Shiraz University of Medical Sciences, 2022)
Background: This study aimed to investigate the impact of frequency and word length on the eye movements in dyslexic students while they were reading Persian textbooks.Methods: The method applied to this study was quasi-experimental. The statistical population consisted of 56 male and female students in first, second, and third grades, referring to Learning Disorder Centers of Educational Organization in 2 and 10 districts in Tehran. Twenty-five students with dyslexia were selected using the available sampling method (participants included 12 boys and 13 girls who were in second, third, fourth, and fifth grade with 6, 8, 8, and 3 students, respectively). The eye-tracking device, SMI-RED-120Hz, was used for data collection. The multivariate analysis of variance (MANOVA) method was applied to analyze the data. Results: There are two significant findings: the effect of words' length on the number of fixation, fixation time, and the number of regression, as well as the effect of words' frequency on the number of fixation, fixation time, and the number of regressions.Conclusion: Frequency and word length on fixation and regression play an important role in the process of reading in dyslexic students.